2022
DOI: 10.1155/2022/4028085
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Perirenal Abscess Caused by Campylobacter and Peptostreptococcus Species

Abstract: Intra-abdominal abscesses mostly derive from the intra-abdominal viscera. Campylobacter spp. are Gram-negative rods which are known to cause oral infections but rarely have been documented to cause extra-intestinal infections resulting in abscesses. We report an atypical case of Campylobacter rectus (C. rectus) and Peptostreptococcus spp. bacteria isolated from a perinephric abscess presenting as abdominal pain. Abscesses originating from outside the gastrointestinal tract have been reported in other similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Anaerobic bacteria of the Peptostreptococcus species are distinguished by their Gram-positive cocci form. It has also been discovered that these species are a typical component of the oral cavity’s flora ( 55 ).…”
Section: Oral Bacteria Associated With Osccmentioning
confidence: 99%
“…Anaerobic bacteria of the Peptostreptococcus species are distinguished by their Gram-positive cocci form. It has also been discovered that these species are a typical component of the oral cavity’s flora ( 55 ).…”
Section: Oral Bacteria Associated With Osccmentioning
confidence: 99%
“…Campylobacter is an important zoonotic pathogen and is often considered to be one of the leading causes of bacterial foodborne illness globally ( 1 3 ). They are microaerophilic and grow under microaerobic conditions (10% CO 2 , 5% O 2 ) at 42°C ( 4 ). Campylobacter can cause gastrointestinal infections with symptoms of inflammatory, bloody diarrhea or dysentery syndromes, mostly consisting of cramps, fever, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Campylobacter infections are associated with abortion in primates and ruminants by invading the genital tract ( 3 , 16 ). Meanwhile, Hasel et al observed the heavy colonization of Campylobacter in human kidney abscesses ( 4 ). Other studies have also found Campylobacter in abscess infections of the head, brain, and chest walls ( 4 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation